2017
DOI: 10.1002/bbb.1803
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impacts of wood pellet demand on forest dynamics in southeastern United States

Abstract: The export of wood pellets from the southeastern United States (USA) has grown significantly in recent years, following rising demand from Europe. Increased wood pellet demand could lead to spatially variable changes in timberland management and area in the USA. This study presents an assessment of the impacts of increasing wood pellet demand (an additional 11.6 Mt by 2030) on land‐use dynamics, taking into account developments in other wood product markets as well as expected changes in other land uses. An ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 46 publications
0
47
1
Order By: Relevance
“…Land‐use projections were found to be most accurate for the land use types lowland hardwood forest, urban and cropland, and results were less accurate for mixed forest, natural and plantation pine forest, pasture and nonforest vegetation. The accuracy of PLUC is reduced with increasing spatial resolution, and sensitivity analyses indicated that PLUC output at a resolution higher than a county‐sized level is less accurate (Duden et al, ). This necessitated the aggregation of species richness index to a window size comparable to the average county in the study region (about 1,500 km 2 ), in order for the visualization of the results to be consistent with the uncertainty in the land‐use projections.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Land‐use projections were found to be most accurate for the land use types lowland hardwood forest, urban and cropland, and results were less accurate for mixed forest, natural and plantation pine forest, pasture and nonforest vegetation. The accuracy of PLUC is reduced with increasing spatial resolution, and sensitivity analyses indicated that PLUC output at a resolution higher than a county‐sized level is less accurate (Duden et al, ). This necessitated the aggregation of species richness index to a window size comparable to the average county in the study region (about 1,500 km 2 ), in order for the visualization of the results to be consistent with the uncertainty in the land‐use projections.…”
Section: Discussionmentioning
confidence: 99%
“…Rectangles symbolize maps, and the stack of rectangles symbolizes individual species habitat maps of 811 species included in the analysis. Arrows symbolize adaptations to the maps; 1) modelling of wood pellet demand scenarios using the economic wood market model SRTS and land‐use change model PLUC to create different land‐use projections up to 2030 (see Duden et al, ), 2) summing of species potential habitat maps taken from US‐GAP (McKerrow et al, ) to create maps of potential species richness and 3) spatial analysis using a moving window approach to create spatially explicit projections of species richness index up to 2030…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations